Strategies for the Academic Administration According to the Digital Citizenship Concept of Educational Institutions under the Nakhon Ratchasima Primary Educational Service Area Office - Yodying, Chulalux; Phoorungrueng, Suphap; Thee-asana, Siri (Journal of Education Studies, Chulalongkorn University, 2023)
This research aimed to 1) study the conceptual framework of Academic Administration and Digital Citizenship, 2) study the needs of Academic Administration based on the concept of Digital Citizenship in schools in the Nakhon Ratchasima Primary Educational Service Area Office, and 3) develop strategies for Academic Administration based on the concept of Digital Citizenship. The sample groups for this research consisted of 306 schools, and the study employed multi-stage random sampling. The contributors were school directors and teachers. The research instruments consisted of conceptual framework evaluation, a questionnaire, and strategy evaluation. The data was analyzed using frequencies, percentages, means, standard deviations, PNI modified, and content analysis. The results of the study were as follows: 1. The Conceptual Framework consisted of the following: 1.1) Academic Administration, including (a) Curriculum Development for the schools, (b) Teaching and Learning Management, and (c) Measurements & Evaluation, as well as 1.2) Digital Citizenship, which consisted of three aspects: (a) developing self-respect and respecting others, (b) learning and self-development, and (c) being responsible and being secure. 2.The Development Priority Needs were: 2.1) Academic Administration, including the development of school curriculum, and 2.2) Digital Citizenship, such as taking responsibility and being secure. 3. Finally, The Strategies for Development were comprised of two aspects: 3.1) the strategies for developing the school Administrators, which were composed of three main strategies, with 14 sub-strategies, and 79 approaches, and 3.2) The Evaluation of Possibility and Feasibility, which was at a ‘High’ level.